2018
DOI: 10.17582/journal.pjz/2018.50.5.1921.1927
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Various Udder Measurements and Milk Components in Morkaraman, Tuj and Awassi Sheep

Abstract: Authors' Contribution SO conceived the idea. DT and SO designed the study and wrote the manuscript. NE and MY edited the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
2
2
0
1
Order By: Relevance
“…In a study conducted by Türkyılmaz et al [27] in Morkaraman sheep, similar to the findings in the present study, a positively correlation was observed between the udder dept and solid non-fat, density, protein, lactose, ash, and also udder width and fat, solid non-fat, lactose, density, protein, lactose, ash (P<0.05, P<0.01). In the study, it was determined that the effect of udder types (type 1, type 2, type 3, type 4 and type 6) on fat and conductivity was found to be significant (P<0.05).…”
Section: Physicochemical Properties Of Milksupporting
confidence: 92%
“…In a study conducted by Türkyılmaz et al [27] in Morkaraman sheep, similar to the findings in the present study, a positively correlation was observed between the udder dept and solid non-fat, density, protein, lactose, ash, and also udder width and fat, solid non-fat, lactose, density, protein, lactose, ash (P<0.05, P<0.01). In the study, it was determined that the effect of udder types (type 1, type 2, type 3, type 4 and type 6) on fat and conductivity was found to be significant (P<0.05).…”
Section: Physicochemical Properties Of Milksupporting
confidence: 92%
“…Both types of udders had low and oblique teats, while the second type was cylindrical and the third type was pear-shaped. The third udder type (70.3%) was found to be the most common in Morkaraman, Tuj and Awassi sheep breeds and the most optimal and acceptable for machine milking (Türkyýlmaz et al 2018). Similar findings were found in studies reporting the 3 rd type as the most common udder type in various sheep breeds (Kukovics et al 2006;Kaygýsýz and Dag, 2017;Prpic et al 2020).…”
Section: Udder Typesupporting
confidence: 79%
“…Figure . Udder and teat measurements (Türkyılmaz et al, 2018) Şekil. Meme ve meme başı ölçümleri (Türkyılmaz ve ark., 2018)…”
Section: Methodsunclassified